Transferring Therapeutic Communication From Simulation to First Clinical Placement: A Qualitative Description of Undergraduate Nursing Students’ Experiences - Israa A. M. Abuijlan; Fatma M. Ibrahim; Eman Abdelaziz Rashad Dabou; Rachel James; Shaimaa Hashem Elsalous; Shaimaa Abdelsamad; Amal Mohammed Abdallah Al Balushi (Global Qualitative Nursing Research, 2026)
Simulation-based learning is widely used to prepare nursing students for therapeutic communication, but transfer is often treated as if students acquire decontextualized skills in the laboratory and then apply them in clinical practice. This qualitative descriptive study explored how undergraduate nursing students experienced the transition from communicating with simulated patients to communicating with real patients during early clinical practice. Fifteen third-year Bachelor of Science in Nursing students in the United Arab Emirates who had completed the required Adult Health Nursing I simulation component and an initial medical-surgical clinical rotation participated in three face-to-face focus groups. Data were analyzed inductively using reflexive thematic analysis. The overarching interpretation was that students moved from prepared encounters in simulation to situated responsiveness in clinical practice. Three themes explained this shift: encountering unplanned patient agency, becoming accountable for one’s response, and communicating within institutional opacity. Simulation supported foundational communication practices but did not fully reproduce the emotional, relational, cultural, and organizational conditions of real patient communication. Findings suggest that simulation-to-practice transfer should be supported through progressively complex patient portrayals, explicit orientation to communication boundaries and workflows, and structured post-clinical reflection.